The Influence of Candidates' Ethnic Identity on Student Voting Participation in the Student Executive Board Elections of the Faculty of Law, UNJA - Putri GL Sianturi; Hatta Abdi Muhammad; Cholillah Suci Pratiwi; Dori Efendi (Greenation Research & Yayasan Global Resarch National, 2025)
Student political participation in campus elections (Pemira) is influenced by various factors, one of which is the perception of the candidates' ethnic identity. This study aims to analyze the extent to which ethnic identity influences student voting behavior in Pemira BEM Faculty of Law, University of Jambi. The method used is quantitative research with a survey technique through a questionnaire distributed to 350 active student respondents. Data were analyzed using correlation tests and simple linear regression to examine the relationship between the candidates' ethnic identity and voter participation levels. The results show that ethnic identity has a significant influence on students' voting decisions, so that students' political preferences are not entirely based on the capabilities and vision and mission of the candidates, but also on the proximity of their social identities. These findings indicate that campus political dynamics are still influenced by group identity factors, and more inclusive political education is needed so that voter participation is more oriented towards the competencies and ideas of the candidates.